Reliability of a method to conduct upper airway analysis in cone-beam computed tomography - Karen Regina Siqueira de Souza; Paula Vanessa Pedron Oltramari-Navarro; Ricardo de Lima Navarro; Ana Cláudia de Castro Ferreira Conti; Marcio Rodrigues de Almeida (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to assess the reliability of a method to measure the following upper airway dimensions: total volume (TV), the nasopharyngeal narrowest areas (NNA), and the oropharyngeal narrowest areas (ONA). The sample consisted of 60 cone-beam computed tomography (CBCT) scans, evaluated by two observers twice, using the Dolphin 3D software (Dolphin Imaging & Management solutions, Chatsworth, California, USA), which afforded image reconstruction, and measurement of the aforementioned dimensions. The data was submitted to reliability tests, by the intraclass correlation coefficient (ICC), and the Bland & Altman agreement tests, with their respective confidence intervals (CI) set at 95%. Excellent intra- and interobserver reliability values were found for all variables assessed (TV, NNA and ONA), with ICC values ranging from 0.88 to 0.99. The data demonstrated an agreement between the two assessments of each observer and between the first evaluations of both observers, thus confirming the reliability of this methodology. The results suggest that this methodology can be used in further studies to investigate upper airway dimensions (TV, NNA, and ONA), thereby contributing to the diagnosis of upper airway obstructions.